Diffusing MNE subsidiary initiatives across national cultural distance: The role of organizational values sharing and knowledge sharing - Williams, Christopher; Kumar, Maya (Management international / International Management / Gestiòn Internacional, 2022)
We investigate how internal sharing of values and knowledge in multinational enterprises (MNEs) influences the relationship between external national cultural distance and the adoption of subsidiary initiatives by headquarters. We draw on management control and knowledge-based theories and use a sample of 111 subsidiaries across various cultures and industries in the empirical test. As hypothesized, national cultural distance has a negative impact on subsidiary initiative diffusion, while organizational values sharing and knowledge sharing have positive effects. Internal values sharing does little to overcome the negative impact of national cultural distance, while internal knowledge sharing dampens this effect. Implications for MNE managers and research are discussed.